Investigation of potentially pathogenic multidrug-resistant bacteria and antibiotic-resistance genes in the Nha Trang Sea, Vietnam - Bui, Duc Thinh; Tran, Son Hoang; Nguyen, Quang Huy (Academia Journal of Biology, 2025)
This study investigated the circulation of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the Nha Phu and Bich Dam areas, the Nha Trang Sea, Vietnam, a region experiencing considerable environmental stress due to urbanization and tourism. Multidrug-resistant bacteria including Escherichia coli, Enterobacter hormaechei, Proteus mirabilis, Pseudomonas aeruginosa, Vibrio alginolyticus, Bacillus cereus, and Micrococcus luteus were detected in sediment and water samples. The abundance of marine microbiome was from 3.8 × 109 to 1.5 × 109 copies/mL in surface water samples and in the sediment and from 9.9 × 107 to 2.6 × 109 copies/g in sediments. Among the four target ARGs, the sul1 and sul2 genes associated with sulfonamides resistance were detected in both water and sediment samples ranging from 2.3 × 100 to 4.5 × 103 copies/mL, and from 2.0 × 103 to 4.7 × 105 copies/g in water and sediment samples, respectively. For tetracycline resistance, tetQ and tetM were detected in 60% and 100% studied samples. The abundance of these genes was up to 1.7 × 10² copies/mL in water samples, and 1.1 × 105 copies/g in sediments. The class 1 integron-integrase gene intI1 displayed from 6.2 × 10² to 2.6 × 10³ copies/mL and from 4.8 × 104 to 8.2 × 105 copies/g in water and sediment samples, respectively. Our findings emphasize the risk of ARB and their associated ARGs being transmitted in the marine environments of the Nha Trang Sea through the assistance of mobile genetic elements.